Influence of laser power on microstructure and performance of SiC/Ti composite fabricated through selective laser melting - Jun Fang; Yong Chai Tan; Youwen Yang; Yuwei Yi; Dongsheng Wang; Enping Wei; Peipei Zhang; Xiang Li (Journal of Materials Research and Technology)
SiC particle-reinforced titanium (Ti) composites fabricated through Selective Laser Melting (SLM) demonstrate significant improvements in mechanical and tribological properties. However, the influence of SLM processing on microstructure and property evolution remains underexplored. This study investigates the microstructural development of 1 wt % SiC-reinforced Ti composites processed at varying laser scanning power and their resulting mechanical and tribological performance. Results indicate that mechanical properties initially improve with increased scanning power but deteriorate beyond a threshold. Optimal laser power was determined at 140 W where the composites achieved a relative density of 99.6 %, hardness of 344 HV, and tensile strength of 1097 MPa representing enhancements of 66.7 % in hardness and 74.5 % in tensile strength over unreinforced Ti. Tribological performance was also optimized at this power. Reactions between SiC and Ti during SLM enhanced hardness and strength. These findings highlight how scanning power affects microstructural evolution, providing critical insights for optimizing the performance of SiC/Ti composites in advanced engineering applications.